Answer:
![a=-23\\\\b=28](https://img.qammunity.org/2021/formulas/mathematics/college/pong3bydygtnilk0wy9ztz84ph8f6835r6.png)
Explanation:
Let's start by using distributive multiplication:
![(a\pm b)(c\pm d)=ac\pm ad \pm bc \pm bd](https://img.qammunity.org/2021/formulas/mathematics/college/j8dva9afnapo5i49hesen0vmboq9nscwht.png)
So:
![(5x-4)(3x+7)=15x^2+35x-12x-28\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/3vweblftcxmbkib9hahyb1p3cintt2p8je.png)
Grouping like terms:
![15x^2 +(35x-12x)-28\\\\15x^2+23x-28](https://img.qammunity.org/2021/formulas/mathematics/college/cxjlacjgov9x3mbmobv30muur09655kwim.png)
Now,
is equal to:
![15x^2-ax-b](https://img.qammunity.org/2021/formulas/mathematics/college/8i4vsth2nts5l4hw35sig0maz7qp4pscy8.png)
In this sense:
![15x^2+23x-28=15x^2-ax-b](https://img.qammunity.org/2021/formulas/mathematics/college/ht6cgh20enw38ki2r8ml743cs5xsaj51la.png)
In order to satisfied the equality:
![23x=-ax\hspace{10}(1)\\\\and\\\\-28=-b\hspace{10}(2)](https://img.qammunity.org/2021/formulas/mathematics/college/kvglijxepwapn2np6vvfn55s9gb28yd9sc.png)
Hence, from (1), let's solve for a:
![23x=-ax\\\\-a=(23x)/(x) \\\\-a=23\\\\a=-23](https://img.qammunity.org/2021/formulas/mathematics/college/w1b61nkyjsr26kvubijpudkohmuemecu2x.png)
And from (2), let's solve for b:
![-28=-b\\\\b=28](https://img.qammunity.org/2021/formulas/mathematics/college/9jo4ha1c9et7iepz2ahvq3p2p690mhn2p2.png)
Let's verify the result evaluating the values of a and b into the original equation:
![(5x-4)(3x+7)=15x^2+23x-28=15x^2 -ax -b\\\\(5x-4)(3x+7)=15x^2+23x-28=15x^2 -(-23)x -(28)\\\\(5x-4)(3x+7)=15x^2+23x-28=15x^2 +23x -28](https://img.qammunity.org/2021/formulas/mathematics/college/eknjxvkv8nlj344tzlyt24kdy4roblnv78.png)
As you can see, the values satisfy the equation, therefore, we can conclude they are correct.